Interpersonal communication anxiety as a mediator of the relationship between self-control and phubbing behavior in college students - Rahmah Saniatuzzulfa; Gita Aulia Nurani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
Phubbing behavior has been linked to both deficits in self-regulation and heightened interpersonal communication anxiety. This study aimed to examine the mediating role of interpersonal communication anxiety in the relationship between self-control and phubbing behavior among university students. A total of 217 participants were selected using purposive sampling. Three validated instruments were employed: the Generic Scale of Phubbing (GSP; α = 0.825), the Self-Control Scale (α = 0.856), and the Interpersonal Communication Anxiety Scale (α = 0.813). Data were analyzed using mediation analysis via JASP and PROCESS in SPSS. The findings revealed a significant relationship between self-control and phubbing behavior, with interpersonal communication anxiety acting as a partial mediator (p < 0.05). Specifically, the indirect effect (–0.007) was smaller than the direct effect (–0.056), indicating partial mediation. Increases in self-control were associated with a reduction in interpersonal communication anxiety (β = –0.04), which in turn was linked to decreased phubbing behavior (β = –0.16). Collectively, self-control and interpersonal communication anxiety accounted for 17.3% of the variance in phubbing behavior. These findings underscore the importance of enhancing self-regulation strategies among students to mitigate communication-related anxiety and reduce phubbing tendencies, thereby fostering more engaged and meaningful interpersonal interactions.